The fishes of the Farson Cutoff Fishbed, Bridger Formation (Eocene), greater Green River Basin, Wyoming, U. S. A. Issue 6 (1st November 2016) - Divay, Julien D.; Murray, Alison M.
ABSTRACT: The Bridger Formation of the early middle Eocene of Wyoming has been studied for its sedimentology, paleobotany, herpetofauna, and mammalian fauna. Although several taxa have been erected based on its abundant fish material, there has been little work on Bridger Formation fishes other than these initial descriptions. We here describe the fishes of the Farson Cutoff Fishbed, a single Bridger Formation locality in the Bridger Basin. This material is almost entirely disarticulated and has a notably low taxonomic diversity, representing only three taxa: Lepisosteidae, Phareodus, and Astephus . However, a wide variety of elements are three-dimensionally preserved, showing details that are not visible in articulated specimens and providing insight on the internal anatomy of some elements. The longevity and growth rate of the Bridger Formation catfish Astephus were compared with those of the Cypress Hills Formation Astephus . Longevities were found to be similar, but two distinct growth rates were found in the Cypress Hills material, supporting the hypothesis that two Astephus taxa were present in that formation. The Bridger Formation Astephus had a similar growth rate to the smaller Cypress Hills Formation catfish Astephus taxon B, whereas the larger Astephus taxon A had a significantly faster growth rate. We here interpret the low taxonomic diversity of the Bridger Formation assemblage as a paleoenvironmental indication of hypoxic conditions in the depositional environment. The Farson Cutoff Fishbed probably represents poorly oxygenated backwaters that would have been susceptible to becoming isolated and infilled, preserving a low diversity of fishes capable of sustaining hypoxic conditions. Citation for this article: Divay, J. D., and A. M. Murray. 2016. The fishes of the Farson Cutoff Fishbed, Bridger Formation (Eocene), greater Green River Basin, Wyoming, U.S.A. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2016.1212867.